2021
DOI: 10.1128/aem.01460-21
|View full text |Cite
|
Sign up to set email alerts
|

Using Stable Isotope Probing and Raman Microspectroscopy To Measure Growth Rates of Heterotrophic Bacteria

Abstract: The suitability of stable isotope probing (SIP) and Raman microspectroscopy to measure growth rates of heterotrophic bacteria at the single-cell level was evaluated. Label assimilation into E. coli biomass during growth on a complex 13 C-labeled carbon source was monitored in time course experiments. 13 C-incorporation into various biomolecules was measured by spectral “red shifts” of Raman-scattered emissions. The 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…For example, Li et al (2012) demonstrated that resonance Raman spectra of carotenoids can quantify dissolved inorganic carbon assimilation by individual cyanobacteria and coastal phytoplankton cells incubated with 13 C-bicarbonate. Building on this advance, Taylor et al (2017) and Weber et al (2021) demonstrated that SIP-Raman accurately measures growth rates in individual cells of photoautotrophs and heterotrophs, respectively. Growth rates have also been reported in nanoSIMS studies based on enrichment ratios ( Foster et al, 2011 , 2021 ).…”
Section: Investigating Microbial Composition and Activity Using Confo...mentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Li et al (2012) demonstrated that resonance Raman spectra of carotenoids can quantify dissolved inorganic carbon assimilation by individual cyanobacteria and coastal phytoplankton cells incubated with 13 C-bicarbonate. Building on this advance, Taylor et al (2017) and Weber et al (2021) demonstrated that SIP-Raman accurately measures growth rates in individual cells of photoautotrophs and heterotrophs, respectively. Growth rates have also been reported in nanoSIMS studies based on enrichment ratios ( Foster et al, 2011 , 2021 ).…”
Section: Investigating Microbial Composition and Activity Using Confo...mentioning
confidence: 95%
“…Unique to CRM, a researcher can identify specific microbial taxa within a microscopic field using FISH and the instrument’s epifluorescence optics and then immediately switch optical paths to obtain Raman spectra from each target in a matter of seconds to minutes (Raman-FISH) ( Huang et al, 2007 ). The automated microscope stage can visit each target using stored x-y coordinates or create fixed-point gridded maps ( Taylor, 2019 ; Weber et al, 2021 ), similar to grid systems in MSI. Sampling by Raman spectroscopy is usually non-destructive, so samples can be subjected to other downstream analyses.…”
Section: Investigating Microbial Composition and Activity Using Confo...mentioning
confidence: 99%
See 1 more Smart Citation
“…New diagnostic techniques have recovered complex microbiomes in microbial eukaryotes (Lanzoni et al, 2019; Rossi et al, 2019). Determining the fraction of these that are true symbionts vs. transient associations or ingested prey will require advanced microscopy methods such as Raman spectroscopy (Weber et al, 2021) to track the exchanges of metabolic products between partners.…”
Section: Other Types Of Symbionts In Free‐living Anaerobic Ciliatesmentioning
confidence: 99%
“…Weber et al. explored the utility of Raman microspectroscopy coupled with stable isotope probing for monitoring the growth rates of heterologous bacteria at single-cell resolution, based on the 13 C- and 12 C-isotopologues of the amino acid phenylalanine [ 267 ], identifiable by the strong phenylalanine ring breathing modes 966 and 1,002 cm −1 ). Using a robust curve fitting process for precise deconvolution of partially overlapping peaks, the identified peaks provided an accurate reporter probe for quantification of cellular isotope fractional abundances (f cell ) for complex 13 C-labelled carbon source assimilation in E. coli in time-course experiments.…”
Section: Future Perspectives: Label Free Microspectroscopic Analysismentioning
confidence: 99%